(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This work described the form and content of Tennessee Williams’ Summer and Smoke, with a critical analysis of its historical, cultural and biographical context, as well as a brief notion of its reception and main performances on Broadway and in Brazil. In addition, indicated and critically commented on aspects of the Brazilian translation published, a version that contributed to an unfocused reading of the original text, without being committed to the same dramaturgical elements of Williams, including the change of the original title. Finally, a comparative reading of the second version was presented, never published or performed in Brazilian stages.